Upaya Meningkatkan Hasil Belajar IPA Siswa dengan Menggunakan Metode Demonstrasi pada Kelas VI SD Negeri 01 Durian Tinggi Kecamatan Kapur IX Kabupaten Lima Puluh Kota - Arlis, Arlis (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2018)
This study aims to improve student learning outcomes in class VI State Elementary School 01 Durian Tinggi, because so far classical learning models have not been able to improve student learning outcomes. Data collection is carried out by observation, tests, and observation sheets. The results of the observations are then analyzed and made as an action planning material in the next cycle and then processed in order to draw conclusions. Based on preliminary observations, the initial data obtained about student learning outcomes is that 4 people get very good grades, 7 people get good grades, 20 people get pretty good grades and 1 person gets bad grades. Then the average grade obtained is 73.125. After being implemented in the first cycle, 10 people got very good grades, 15 people got good grades, 6 people got good grades and 1 person got bad grades. The average score of students in cycle I was 78.75. And after implementing the second cycle, 12 people get very good grades, 21 people get good grades, and no one gets good enough grades and less grades. The average score of students in cycle II is 83.98. Based on the results above we can conclude that student learning outcomes have experienced a very good improvement.Implications of the results of Classroom Action Research (CAR) by using the Demonstration method can improve the students’ learning outcomes and also have a positive effect on the activities of class VI students of SDN 01 Durian Tinggi.